As religiões afro-brasileiras no discurso da Igreja Universal do Reino de Deus : a reivindicação de demônio - Dias, Julio Cesar Tavares (2012)
The Universal Church of the Kingdom of God (IURD) is main example of New Pentecostalism and it presents a big growth, looking to incommode Historical Christians groups and making open war against Brazilian cults of African origin. Invasions to sacred spaces and persecution to African religions leaders occurred in Bahia and Rio de Janeiro. Syncretism and bellicosity against African religions are marks constantly pointed like peculiar characteristics to this church. In combat against Devil, this church identified it like entities of religions of African matrix. This thesis results from source that was made at Catedral da Fé and also from analysis of publications of this institution. Our purpose was to analyze the specific demonization of IURD s discourse, which is constructed about afro religions. In elaboration of this thesis, we need to situate historically beginning and developing of IURD, and also of Pentecostal Movement, with which IURD is connected. So, we could to go along our analysis with true safety. Religious intolerance and vilipend were clear in our analysis of publications and exorcism rites by us seen.